PENGEMBANGAN ASESMEN FORMATIF DAN REMEDIASI BERBASIS KOMPUTER PADA POKOK BAHASAN SUHU DAN KALOR SMP KELAS VII - Nurul Kamar; Sentot Kusairi; Siti Zubaidah (Universitas Pendidikan Mandalika, 2016)
Formative assessments developed by teachers are generally conventional. One of the most common constraints on conventional formative assessment is the time to correct the test results long enough, especially for schools with large capacity classes. Therefore the teacher difficulties in providing direct feedback. This paper proposes a computer-based assessment product called ASFORDIASI BEKOM. The application is able to provide formative tests, feedback immediately after conducting tests, and provides remediation materials to help learners learn independently. The design of the study used the Dick & Carey (2001) research and development design which consists of four general stages: preliminary study, preparation, development, and effectiveness test. The study is limited to the third stage of development stage. Based on the validation and trial results of the product, BEKOM ASFORDIASI is considered feasible if used for learning especially on temperature material and calor grade VII SMP.